Development of a Parent Wireless Assistive Interface for Myoelectric Prosthetic Hands for Children - Hiyoshi, Yutaro; Murai, Yuta; Yabuki, Yoshiko; Takahana, Kenichi; Morishita, Soichiro; Jiang, Yinlai; Togo, Shunta; Takayama, Shinichiro; Yokoi, Hiroshi (Frontiers in Neurorobotics, 2018)
In this study, a one-degree-of-freedom myoelectric prosthesis system was proposed using a parent wireless assistive interface (PWAI) that was able to adjust the parameters of the prosthetic hand controller immediately by an external assistant (e.g., the parent of the user). In the PWAI, the myoelectric potential of the upper limb of the use was plotted on an external terminal in real time. Simultaneously, the assistant adjusted the parameters of the prosthetic hand control device and manually manipulated the prosthetic hand. With these functions, children that have difficulty verbally communicating could obtain properly adjusted prosthetic hands. In addition, non-experts could easily adjust and manually manipulate the prosthesis; therefore, training for the prosthetic hands could be performed at home. Two types of hand motion discrimination methods were constructed in this study of the myoelectric control system: (1) a threshold control based on the myoelectric potential amplitude information and (2) a pattern recognition of the frequency domain features. Based on the evaluations, a high discrimination rate was recorded for the adult and child subjects in the threshold control prosthesis system. Furthermore, the high discrimination rate was maintained by sequentially updating the threshold value. In addition, adequate performances for the three motions using the pattern recognition method were obtained.